2006
DOI: 10.1136/qshc.2005.017350
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities for performance improvement in relation to medication administration during pediatric stabilization

Abstract: Objectives: To identify and characterize areas for improvement in the clinical performance of nurses in relation to medication administration. Method: Nurses participated in a simulated pediatric stabilization event which was videotaped. Their clinical performance was evaluated at each of the following steps: (1) communicating and confirming the dose of medication; (2) converting the dose; (3) selecting the correct medications; (4) properly preparing the medication formulation; and (5) measuring medication dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Observational studies of simulated pediatric emergency events have identified problems with dosing of medications 22 and conversion of medication doses ordered in units by weight (eg, milligrams) to the appropriate number of units by volume (eg, milliliters), depending on the formulation of the drug. 23 These studies have also described a prolonged period of time required to calculate doses and administer certain critical medications. 22,23 …”
Section: Statement Of the Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…Observational studies of simulated pediatric emergency events have identified problems with dosing of medications 22 and conversion of medication doses ordered in units by weight (eg, milligrams) to the appropriate number of units by volume (eg, milliliters), depending on the formulation of the drug. 23 These studies have also described a prolonged period of time required to calculate doses and administer certain critical medications. 22,23 …”
Section: Statement Of the Problemmentioning
confidence: 99%
“…23 These studies have also described a prolonged period of time required to calculate doses and administer certain critical medications. 22,23 …”
Section: Statement Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, 32.7% of drug doses drawn up in a syringe were incorrect. 24 One study demonstrated that 81% of nurses were unable to correctly calculate medications 90% of the time and that 43.5% of test scores requiring calculations were below 70% accuracy. 25 In the United States, a nationwide study conducted to assess practices to validate mathematical skills indicated a required passing rate of 80%; no respondent institutions required 100% accuracy.…”
Section: Principles Of Safe Medication Administrationmentioning
confidence: 99%
“…The reference material should therefore include not only the actual milligram dosage of a drug to administer (based on a milligram per kilogram body weight dose), but the exact method of dilution required (if necessary) and also the exact milliliter volume of drug or drug dilution to inject into the patient. 2 Electronic-based drug information systems may also provide significant assistance in this regard.…”
Section: To the Editormentioning
confidence: 99%